2013
DOI: 10.5937/sjm8-4573
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management best practices and firm performance: A universalistic perspective approach

Abstract: The universalistic perspective of human resource management practices perceives that a set of practices can achieve competitive advantage and firm performance. This study sought to investigate the relationship between best human resource practices and firm performance. A descriptive survey research design was used to gather primary data using self-administered questionnaire. The study population (n=312) was comprised of non-executives, executives, managers, and top management from seven major insurance firms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 66 publications
1
6
0
2
Order By: Relevance
“…The results indicated that human resource policies associated with business strategies influences firms' performance through human resource management. Studies have also indicated that best human resource practices like training, recruitment performance appraisal among others significantly influences organizational performance (Beh & Loo, 2013;Amin et al, 2014). From the foregoing we hypothesize that;…”
Section: Human Resource and Firm's Performancementioning
confidence: 97%
See 1 more Smart Citation
“…The results indicated that human resource policies associated with business strategies influences firms' performance through human resource management. Studies have also indicated that best human resource practices like training, recruitment performance appraisal among others significantly influences organizational performance (Beh & Loo, 2013;Amin et al, 2014). From the foregoing we hypothesize that;…”
Section: Human Resource and Firm's Performancementioning
confidence: 97%
“…There have been divergent views on the contributions of human resources to performance in organizations and the literature has referred this as a "black box" that is often mediated by strategy (Orlando & Johnson, 2001;Fey et al 2007). Over the years, scholars have argued whether human resources contribute directly or indirectly to the performance in an organization (Huselid, 1995;Becker & Gerhart, 1996;Orlando & Johnson, 2001;Fey, Yakoushev, Katou, 2008;Beh and Loo, 2013). Some of the studies have tended to confirm the findings by Huselid (1995) that a direct link exists between human resources and organizations performance while the divergent views tends to follow Orlando and Johnson's (2001) arguments that human resource need to be mediated by other variables for it to have a positive effect on organizations performance.…”
Section: Critique Of the Existing Literature And Theoriesmentioning
confidence: 99%
“…The measurement of HRM practice variables used a questionnaire with a Likert rating scale selected and modified from several previous studies (Delery and Doty, 1996;Panayotopoulou et al, 2003;Loo-See and Leap-Han, 2013). The questionnaire consisted of 64 statements and the Likert ratings had seven points.…”
Section: Measurementsmentioning
confidence: 99%
“…Previous research has found that human resource management (HRM) practices have a close relationship with organizational performance (Sonnenfeld and Peiperl, 1988;Huselid, 1995;Delaney and Huselid, 1996;Huselid et al, 1997;Khatri, 2000;Wright et al, 2005;Katou and Budhwar, 2006;Loo-See and Leap-Han, 2013). Many of these studies suggest that, in order to improve performance, organizations need to apply what is called "best practices" (universalistic approaches) in their HRM (Sonnenfeld and Peiperl, 1988;Boxall and Purcell, 2000;Apospori et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies were carried out to establish the relationship between compensation system and OP, result found significant relationship. The study by Beh and Loo (2013) in Asian context Malaysian insurance firms with 312 sample comprises, the top management, executive, nonexecutive and managers. The quantitative result shows that compensation system positively relate to OP.…”
Section: Introductionmentioning
confidence: 99%